Associations of the NRF2/KEAP1 pathway and antioxidant defense gene polymorphisms with chronic obstructive pulmonary disease - Korytina, Gulnaz F.; Kzhyshkowska, Julia (Gene, 2019)
Background and objective - Chronic obstructive pulmonary disease (COPD) is a complex chronic inflammatory disease of the respiratory system affecting primarily distal respiratory pathways and lung parenchyma. This work was designed as a case-control study aimed at investigating the association of the NRF2/KEAP1 signaling system, and antioxidant defense gene polymorphisms with COPD in population from Russia. - Methods - Ten SNPs: NFE2L2 (rs35652124), KEAP1 (rs1048290), MPO (rs2333227), PRNP (rs1799990), PTGR1 (rs2273788), HSPA1A (rs1008438), TXNRD2 (rs1139793), GSR (rs1002149), SIRT2 (rs10410544), and PTGS1 (rs1330344) were genotyped by the real-time polymerase chain reaction (TaqMan assays) in a case-control study (425 COPD patients and 457 controls, from the same region of Russia, representatives of Tatar population). Logistic regression was used to detect the association of SNPs in different models. Linear regression analyses were performed to estimate the relationship between SNPs and lung function parameters and smoking pack-years. - The results - In our population, a significant associations of KEAP1 (rs1048290) (P=0.0015, OR=0.72 in additive model), HSPA1A (rs1008438) (P=0.006, OR=2.26 in recessive model), GSR (rs1002149) (P=0.037, OR=1.31 in additive model) with COPD were revealed. NFE2L2 (rs35652124), PRNP (rs1799990), and HSPA1A (rs1008438) were significantly associated with COPD only in smokers. In nonsmokers, significant association was established for GSR (rs1002149). KEAP1 (rs1048290) was associated with COPD in both groups. The relationship between KEAP1 (rs1048290), NFE2L2 (rs35652124), and HSPA1A (rs1008438) and smoking pack-years was found (P=0.005, P=0.0028, P=0.015). A significant genotype-dependent variation of forced vital capacity and forced expiratory volume in 1s was observed for SIRT2 (rs10410544) (P=0.04), NFE2L2 (rs35652124) (P=0.028), and PRNP (rs1799990) (P=0.044).
Gesehen am 23.05.2019